A Comparative Study on CCS and Renewable Energy in China Challenges and Policy Choices - Meng, Jing; Yang, Qing; Li, Zhi; Wu, Xudong; Chen, Guoqian (Journal of Environmental Accounting and Management, 2026)
With the surging carbon dioxide (CO2) emissions worldwide and the huge energy demand, Chinese government has adopted manystrategies to ensure energy security and to slash CO2emissions, including renewable energy and CCS (carbon capture and storage) technology. A comparative work on CCS and renewable energy technology is conducted in terms of technology, administrative environment, financial support，knowledge diffusion, and market development. Based on the specific situation and available resources, as well as accumulated experiences in renewable energy deployment in China and CCS development in developed countries, recommendations about the choices faced with China for CCS deployment can be summarized as follows: implementing more demonstration projects and collaborating with foreign nations that possess advanced technologies to improve technology maturity, to accumulate engineering experience, to drive down costs and to ensure safety; enforcing a legally binding global climate agreement that may act as a solid force to drive CCS development; building clear financing mechanisms that canincrease public sector financing as well as attract private sector investment; and allowing industrial involvement in policymaking that could help develop a mutual-trust and -benefit relationship between the CCS industries.